PD-1/PD-L1 pathway: an adaptive immune resistance mechanism to immunogenic chemotherapy in colorectal cancer. (3rd June 2018) - Dosset, Magalie; Vargas, Thaiz Rivera; Lagrange, Anaïs; Boidot, Romain; Végran, Frédérique; Roussey, Aurélie; Chalmin, Fanny; Dondaine, Lucile; Paul, Catherine; Marie-Joseph, Elodie Lauret; Martin, François; Ryffel, Bernhard; et al.
ABSTRACT: Background: Chemotherapy is currently evaluated in order to enhance the efficacy of immune checkpoint blockade (ICB) therapy in colorectal cancer. However, the mechanisms by which these drugs could synergize with ICB remains unclear. The impact of chemotherapy on the PD-1/PD-L1 pathway and the resulting anticancer immune responses was assessed in two mouse models of colorectal cancer and validated in tumor samples from metastatic colorectal cancer patients that received neoadjuvant treatment. We demonstrated that 5-Fluorouracil plus Oxaliplatin (Folfox) drove complete tumor cure in mice when combined to anti-PD-1 treatment, while each monotherapy failed. This synergistic effect relies on the ability of Folfox to induce tumor infiltration by activated PD-1 + CD8 T cells in a T-bet dependent manner. This effect was concomitantly associated to the expression of PD-L1 on tumor cells driven by IFN-γ secreted by PD-1+ CD8 T cells, indicating that Folfox triggers tumor adaptive immune resistance. Finally, we observed an induction of PD-L1 expression and high CD8 T cell infiltration in the tumor microenvironment of colorectal cancer patients treated by Folfox regimen. Our study delineates a molecular pathway involved in Folfox-induced adaptive immune resistance in colorectal cancer. The results strongly support the use of immune checkpoint blockade therapy in combination with chemotherapies like Folfox.